Bronchial Artery Embolization for Hemoptysis - Sopko, David R. (Thieme Medical Publishers, 2011)
Bronchial artery angiography with embolization has become a mainstay in the treatment of hemoptysis. Major complications are rare and immediate clinical success defined as cessation of hemorrhage ranges in most series from 85% to 100%, although recurrence of hemorrhage ranges from 10% to 33%. Bronchial artery embolization offers a minimally invasive procedure for even the most compromised patient serving as first-line treatment for hemorrhage as well as providing a bridge to more definitive medical or surgical intervention focused upon the etiology of the hemorrhage. The aim of this article is to summarize the etiologies, pathophysiology, and the diagnostic and management strategies of hemoptysis as related to bronchial artery embolization. In addition, the techniques of arteriography and embolization as well as associated procedural outcomes and complications are delineated.